Treatment method for improving wear resistance and hydrophobicity of titanium alloy surface
The titanium alloy with surface microstructure was prepared by selective laser melting and heat treatment, and the surface gap was filled with polytetrafluoroethylene solution, which solved the problem that the wear resistance and corrosion resistance of titanium alloy materials in seawater environments for a long time, and achieved efficient hydrophobic and wear-resistant effects on the material surface.
Patent Information
- Application Number
- CN202211614055.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-12-15
AI Technical Summary
Existing titanium alloy surface treatment technology is difficult to maintain the material's wear resistance and corrosion resistance for a long time in seawater erosion and corrosion environments.
Titanium alloy with surface microstructure was prepared by selective laser melting, and heat treatment was performed using heating and quenching processes, and finally the gaps of the surface microstructure were filled with polytetrafluoroethylene solution to enhance hydrophobicity.
It significantly improves the hydrophobicity and wear resistance of the surface of titanium alloy materials, and enhances its corrosion resistance and durability in seawater environments.
Smart Images

Figure CN116000313B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy surface treatment, in particular to a treatment method for improving the wear-resistant and hydrophobic properties of the titanium alloy surface. Background Art
[0002] Titanium alloy materials have good application prospects in the fields of aerospace, navigation, military, energy and medical due to their excellent comprehensive mechanical properties (high specific strength, fatigue strength, fracture toughness and high temperature stability) and low density. However, the low hardness, high friction coefficient and poor wear resistance of titanium alloy materials seriously restrict their promotion and application in the above fields. Especially in the working environment with erosion and corrosion such as the ocean, it is necessary to regulate the wear resistance and corrosion resistance of titanium alloy materials through surface treatment technology.
[0003] Improving the hydrophobicity of the surface of titanium alloy materials can effectively reduce the electrochemical corrosion formed on the surface of the material due to the electrolytic cell. At present, there are two main design ideas for improving the wear and corrosion resistance of titanium alloy materials through surface treatment: one is to construct a rough micro-nano structure on the surface of the material with low surface energy to improve the hydrophobicity of the material surface, including etching, anodizing and solution immersion; the other is to modify the rough surface with low surface energy materials, including vapor phase chemical deposition, sol-gel method, layer-by-layer self-assembly technology and electrochemical deposition. The existing surface treatment process can improve the hydrophobic properties of the surface of titanium alloy materials to a certain extent, thereby improving its corrosion resistance. However, the above-mentioned microstructure or modified material has a low interface bonding strength with the matrix material, which is difficult to maintain stably under the action of seawater immersion and scouring, reducing the durability and stability of the corrosion resistance of the material surface. Therefore, in order to improve the durability and wear resistance of the corrosion resistance of the titanium alloy surface, it is very necessary to explore new surface treatment methods.
[0004] The above information disclosed in this Background section is only for enhancement of understanding of the background of the invention and therefore it may contain information that does not form the prior art that is already known to a person of ordinary skill in the art. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention proposes a treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface. By in-situ generating a dense thin layer with both hydrophobic properties and high hardness on the titanium alloy surface, the surface hydrophobicity and wear resistance of the titanium alloy material can be effectively improved, and the wear resistance and corrosion resistance of the titanium alloy material in seawater scouring and corrosive environments and the application prospects can be significantly improved.
[0006] The object of the present invention is achieved through the following technical scheme: a treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface comprises:
[0007] Step 1, preparing a titanium alloy having a surface microstructure by selective laser melting, wherein gaps exist between adjacent micro-convex structures in the surface microstructure;
[0008] Step 2, heat treating the titanium alloy having the surface microstructure by a heating and quenching process;
[0009] Step 3, performing hydrophobic strengthening treatment on the surface of the heat-treated titanium alloy, wherein a polytetrafluoroethylene solution is filled in the gap.
[0010] In the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 1, the titanium alloy powder used for selective laser melting is spherical powder with a particle size distribution of 30 to 75 μm.
[0011] In the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 1, the micro-convex structure includes square protrusions with a size of 1mm×1mm×0.5mm, and the gap between adjacent square columns is 0.3mm.
[0012] In the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 2, an induction heating device is used to heat the titanium alloy with a surface microstructure, and high-purity argon gas is used to protect the sample; the heating power is 5 to 10 kW, heated to 600 to 1000°C and kept warm for 2 to 5 minutes.
[0013] In the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 2, an ethanol solution with a concentration of 20-35wt.% is used as a quenching medium, and the heated titanium alloy is immersed in the quenching medium for quenching treatment, and the immersion time is maintained at 1 to 5 minutes.
[0014] In the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 2, a polytetrafluoroethylene solution with a concentration of 5 to 10 wt.% is used to fill the gaps in the surface microstructure of the quenched titanium alloy, and a blast drying oven is used for drying, and the filling is repeated until the gaps in the surface microstructure of the titanium alloy are completely filled.
[0015] In the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 1, the geometric dimensions of the titanium alloy are 20 mm×20 mm×5 mm.
[0016] Compared with the prior art, the present invention has the following advantages: the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface described in the present invention can not only improve the hydrophobicity of the titanium alloy surface, but also improve its surface wear resistance; in the heat treatment technology, a thin titanium layer with wear-resistant and hydrophobic characteristics is formed in situ on the titanium alloy surface and is tightly combined with the substrate, which can significantly improve the stability and durability of the hydrophobic characteristics of the titanium alloy surface; the surface treatment process of the present invention is simple to operate, time-saving, efficient and of reliable quality, and is suitable for rapid surface treatment to improve its wear resistance and corrosion resistance treatment requirements and improve production efficiency; by filling the micro-convex gaps with hydrophobic polytetrafluoroethylene, hydrophobic substances can be continuously provided to the contact surface during the wear process, giving the contact surface hydrophobic self-healing characteristics, thereby improving the corrosion resistance and durability of the titanium alloy surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work. Moreover, the same reference numerals are used to represent the same components throughout the drawings.
[0018] In the attached picture:
[0019] Figure 1 It is a schematic diagram of the morphology of a titanium alloy according to a treatment method for improving the wear resistance and hydrophobicity of a titanium alloy surface provided by an embodiment of the present invention, wherein (a) is a schematic diagram of the morphology of a titanium alloy surface microstructure prepared by selective laser melting printing, (b) is a schematic diagram of the morphology of a titanium alloy surface microstructure after heat treatment, and (c) is a schematic diagram of the morphology of a titanium alloy surface structure after hydrophobic strengthening; a topological microstructure is constructed on the titanium alloy surface by 3D printing to achieve the synergistic function of a wear-resistant contact surface and a hydrophobic self-healing medium storage; the titanium alloy surface hardness and hydrophobicity are simultaneously enhanced by rapid induction heating and ethanol medium quenching; and a hydrophobic medium is further filled in the microstructure gap to provide a hydrophobic repair function for the wear surface;
[0020] Figure 2It is a schematic diagram of the contact angle of the micro-convex surface of a titanium alloy with a microstructure according to a treatment method for improving the wear resistance and hydrophobicity of a titanium alloy surface provided by an embodiment of the present invention, wherein (a) the contact angle of the micro-convex surface of a titanium alloy printed by selective laser melting, (b) the contact angle of the micro-convex surface of a titanium alloy after heat treatment, and (c) the contact angle of the micro-convex surface of a titanium alloy hydrophobized by polytetrafluoroethylene; the titanium alloy with a topological microstructure after 3D printing exhibits a strong hydrophilic characteristic; the titanium alloy surface after quenching forms a titanium dioxide hydrophobic medium to transform the wettability of the titanium alloy surface into a hydrophobic characteristic; further gap filling and surface coating with a hydrophobic medium strengthen the hydrophobic property and hydrophobic self-repairing function of the titanium alloy surface;
[0021] Figure 3 A schematic diagram showing a comparison of the friction coefficient of a titanium alloy with a microstructure on the surface prepared by a selective laser melting process, the friction coefficient of a titanium alloy treated by induction heating and quenching, and the friction coefficient of a commercial titanium alloy surface according to a treatment method for improving the wear resistance and hydrophobicity of a titanium alloy surface provided by an embodiment of the present invention; the wear resistance of the titanium alloy surface treated by 3D printing shows a slight strengthening effect in the initial stage; and the friction coefficient of the titanium alloy surface treated by quenching shows a significant reduction feature during the entire friction cycle;
[0022] Figure 4 It is a schematic diagram of the surface microstructure of a treatment method for improving the wear resistance and hydrophobicity of a titanium alloy surface provided by an embodiment of the present invention.
[0023] The present invention is further explained below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION
[0024] The following will refer to the attached Figures 1 to 4 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0025] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0026] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0027] In one embodiment, Figures 1 to 4 As shown, the treatment methods for improving the wear resistance and hydrophobicity of titanium alloy surface include:
[0028] Step 1, preparing a titanium alloy having a surface microstructure by selective laser melting, wherein gaps 2 exist between adjacent micro-convex structures 1 in the surface microstructure;
[0029] Step 2, heat treating the titanium alloy having the surface microstructure by a heating and quenching process;
[0030] Step 3, performing hydrophobic strengthening treatment on the surface of the heat-treated titanium alloy, wherein the gap 2 is filled with a polytetrafluoroethylene solution.
[0031] In a preferred embodiment of the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 1, the titanium alloy powder used for selective laser melting is a spherical powder with a particle size distribution of 30 to 75 μm.
[0032] In a preferred embodiment of the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 1, the micro-convex structure 1 includes square protrusions with a size of 1 mm×1 mm×0.5 mm, and the gap 2 between adjacent square columns is 0.3 mm.
[0033] In the preferred embodiment of the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 2, an induction heating device is used to heat the titanium alloy with a surface microstructure, and high-purity argon gas is used to protect the sample; the heating power is 5 to 10 kW, heated to 600 to 1000°C and kept warm for 2 to 5 minutes.
[0034] In a preferred embodiment of the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 2, an ethanol solution with a concentration of 20-35wt.% is used as a quenching medium, and the heated titanium alloy is immersed in the quenching medium for quenching treatment, and the immersion time is maintained at 1 to 5 minutes.
[0035] In a preferred embodiment of the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 2, a polytetrafluoroethylene solution with a concentration of 5 to 10 wt.% is used to fill the gaps 2 of the surface microstructure of the titanium alloy that has been quenched, and the solution is dried in a blast drying oven, and the filling is repeated until the gaps 2 of the surface microstructure of the titanium alloy are completely filled.
[0036] In a preferred embodiment of the treatment method for improving the wear resistance and hydrophobicity of the titanium alloy surface, in step 1, the geometric dimensions of the titanium alloy are 20 mm×20 mm×5 mm.
[0037] In one embodiment, the size of the surface microstructure is in the range of millimeter to micrometer.
[0038] Example 1
[0039] This embodiment provides a method for improving the wear resistance and hydrophobicity of the titanium alloy surface, comprising the following steps:
[0040] Step 1, preparation of titanium alloy sample with surface microstructure: using selective laser melting process to print titanium alloy sample with square micro-convex topological structure on the surface, there is a certain width of gap 2 between adjacent micro-convex structures 1, such as Figure 4 shown.
[0041] Specifically, step 1 includes the following steps: first, select titanium alloy spherical powder with a powder particle size of 30-75μm as the printing raw material; then set the printing program parameters according to the design drawing parameters, determine the printing laser power and the spot movement rate to be 500-1500W and 100-1000mm / s respectively, and obtain a titanium alloy pattern with a square micro-convex structure 1 on the surface.
[0042] Step 2, heat treatment of titanium alloy material: using induction heating to quickly heat the titanium alloy sample with microstructure on the surface under a protective atmosphere, and performing ethanol medium quenching treatment on the heated titanium alloy sample.
[0043] Specifically, step 2 includes the following steps: first, placing the selected laser melting printed titanium alloy sample in an acetone solution and using ultrasonic cleaning to clean the surface and dry it; then setting the induction heating power and temperature to 500-1500W and 600-1000°C according to the size of the titanium alloy sample; using argon as a protective atmosphere to quickly heat to the set temperature and keep it warm for 2-5 minutes. Using anhydrous ethanol reagent to prepare a quenching reagent with a concentration of 20-45wt%, then immersing the heated titanium alloy sample in the quenching solution for quenching treatment for 2-5 minutes, and obtaining a surface having a titanium oxide and carbide thin layer structure.
[0044] Step 3, strengthening the surface hydrophobic property: filling the gap 2 of the topological structure on the surface of the heat-treated titanium alloy sample with a polytetrafluoroethylene solution, and filling the gap 2 multiple times to achieve full filling of the gap 2.
[0045] Specifically, step 3 includes the following steps: using a 60% polytetrafluoroethylene solution to dilute a 5-10wt.% impregnation solution, immersing the heat-treated titanium alloy sample in the solution to fill the surface gap 2 and drying it at 60°C; repeating the above immersion and drying treatment on the dried titanium alloy sample until the gap 2 is fully filled with the hydrophobic medium.
[0046] In one embodiment, in step 1, the process parameters of the selective laser melting are: laser power 500-1500 W, spot diameter 0.06-0.1 mm, and spot moving speed 100-1000 mm / s.
[0047] In one embodiment, in step 1, the powder parameters selected for selective laser melting are: TC4 titanium alloy spherical powder, powder particle size 30-75 μm, median diameter 50 μm.
[0048] In one embodiment, in step 2, the process parameters of induction heating are: induction current 5-15A, argon gas flow rate 10ml / min.
[0049] In one embodiment, in step 2, the induction heating process is as follows: heating temperature 600-1000° C., and holding time 2-5 minutes.
[0050] In one embodiment, in step 2, the composition parameters of the quenching medium are: 500 ml of a quenching solution with a concentration of 20-45 wt % of anhydrous ethanol.
[0051] In one embodiment, in step 2, the quenching process parameters are: the induction heated titanium alloy material is completely immersed in 500 ml of quenching medium for 2-5 minutes.
[0052] In one embodiment, in step 3, the hydrophobic medium component parameter is: a polytetrafluoroethylene solution with a mass fraction of 60wt.% is used to prepare an aqueous solution with a concentration of 5-10wt.%. Further, in step 3, the hydrophobic strengthening treatment process is: immersing the quenched titanium alloy material in the above-prepared polytetrafluoroethylene solution for 5-10 minutes, taking it out and placing it in a blast drying oven for drying, and repeating the above operation multiple times until the microstructure gap 2 on the titanium alloy surface is fully filled with the hydrophobic medium.
[0053] In one embodiment, the method includes: using laser selective melting technology to prepare TC4 titanium alloy with microstructure on the surface; induction heating the titanium alloy under argon protection to quickly heat the surface of the titanium alloy to 1000°C, quenching the sample in a solution medium containing ethanol (anhydrous ethanol concentration, 20-35wt.%) to achieve quenching and hardening of the titanium alloy surface, while the ethanol in the quenching medium reacts with the titanium element on the surface of the titanium alloy under high temperature to in-situ generate a dense thin layer of titanium carbide and titanium dioxide to change the surface wetting characteristics and mechanical properties of the titanium alloy; using polytetrafluoroethylene solution (PTFE concentration, 10-20wt.%) to fill the microstructure gap 2 on the surface of the titanium alloy sample to further enhance its surface hydrophobic persistence. Compared with the existing wear-resistant coating technology, the surface treatment technology in the present invention has a simple and efficient operation process, and the thin layer with hydrophobic and hardening effects generated in situ on the surface of the titanium alloy is tightly and stably combined with the titanium alloy matrix, significantly improving its surface hydrophobic properties and wear resistance. This surface treatment process is of great value in improving the wear and corrosion resistance of equipment in marine environments.
[0054] Although the embodiments of the present invention are described above in conjunction with the accompanying drawings, the present invention is not limited to the above specific embodiments and application fields, and the above specific embodiments are only illustrative and instructive, rather than restrictive. A person of ordinary skill in the art can also make many forms under the guidance of this specification and without departing from the scope of protection of the claims of the present invention, all of which belong to the protection of the present invention.
Claims
1. A method for improving the wear resistance and hydrophobicity of titanium alloy surface, characterized in that: It includes the following steps, Step 1, preparing a titanium alloy having a surface microstructure by selective laser melting, wherein gaps exist between adjacent micro-convex structures in the surface microstructure; Step 2, heat treating the titanium alloy having the surface microstructure by a heating and quenching process; Step 3, performing a hydrophobic strengthening treatment on the surface of the heat-treated titanium alloy, wherein a polytetrafluoroethylene solution is filled in the gap; In step 2, an induction heating device is used to heat the titanium alloy with a surface microstructure, and high-purity argon gas is used to protect the sample; the heating power is 5-10kW, and the sample is heated to 600-1000°C and kept warm for 2-5 minutes; In step 2, an ethanol solution with a concentration of 20-35 wt.% is used as a quenching medium, and the heated titanium alloy is immersed in the quenching medium for quenching treatment, and the immersion time is maintained at 1-5 minutes.
2. The method for improving the wear resistance and hydrophobicity of the titanium alloy surface according to claim 1, characterized in that: In step 1, the titanium alloy powder used for selective laser melting is spherical powder with a particle size distribution of 30-75 μm.
3. The method for improving the wear resistance and hydrophobicity of the titanium alloy surface according to claim 1, characterized in that: In step 1, the micro-convex structure includes square protrusions with a size of 1 mm×1 mm×0.5 mm, and a gap between adjacent square columns is 0.3 mm.
4. The method for improving the wear resistance and hydrophobicity of the titanium alloy surface according to claim 1, characterized in that: In step 2, a polytetrafluoroethylene solution with a concentration of 5 to 10 wt.% is used to fill the gaps in the surface microstructure of the quenched titanium alloy, and a blast drying oven is used for drying, and the filling is repeated until the gaps in the surface microstructure of the titanium alloy are completely filled.
5. The method for improving the wear resistance and hydrophobicity of the titanium alloy surface according to claim 1, characterized in that: In step 1, the geometric dimensions of the titanium alloy are 20 mm × 20 mm × 5 mm.